PENGARUH PENAMBAHAN TEPUNG BUAH PEPAYA (Carica papaya L.) PADA PAKAN TERHADAP PENINGKATAN KECERAHAN IKAN MASKOKI (Carassius auratus) - Hasyiati Aini; Nanda Diniarti; Fariq Azhar (Universitas Sriwijaya, 2021)
Goldfish (Carassius auratus) are in great demand by cultivators and ornamental fish enthusiasts. The color of ornamental fish is one of the most influential factors on the selling price of the fish. Papaya can be used as an alternative to improve the color quality of fish. This study aims to analyze the effect of adding papaya flour to the feed on increasing the brightness of goldfish and to conclude the appropriate dose of papaya flour to increase the color brightness of goldfish). This research was conducted from April to June 2021 at the Laboratory of the Aquaculture Study Program, Faculty of Agriculture, University of Mataram. The method used is the experimental method and Completely Randomized Design (CRD) with four treatments and three replications, namely P1 (without the addition of papaya flour), P2 (addition of 15% papaya flour), P3 (20% addition of papaya flour), P4 (addition of papaya flour 25%). Goldfish's highest brightness level is at P4 with a value of 87.02 and the lowest is at P1 with a value of 72.06. The highest carotenoid content was at P4 with a value 9.81 mol/g while the lowest was at P1 with a value of 4.52 mol/g.Keywords : Brightness, Carotenoids, Goldfish, Papaya Flour